An Automated End-to-End Lecture Capturing and Broadcasting System - Zhang, Cha; Rui, Yong; Crawford, Jim; He, Li-wei (Association for Computing Machinery, Inc., 2008)
Increasingly popular, lectures are given before a live audience, while simultaneously being viewed remotely and recorded for subsequent on-demand viewing over the Internet. Providing such services, however, is often prohibitive due to the cost of labor-intensive content capturing and pre-/post-production. This paper presents a complete end-to-end system that is fully automated and supports capturing, broadcasting, viewing, archiving and search. Specifically, we describe a system architecture that minimizes the pre- and post-production time, and a fully automated lecture capturing system called iCam2, which synchronously captures all the contents of the lecture, including audio, video and visual aids. As no staff is needed during the lecture capturing and broadcasting process, the operation cost of our system is negligible. The system has been used on a daily basis for more than 4 years, during which 522 lectures were captured with 20,000+ online viewers.